2017
DOI: 10.1186/s12882-016-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia increases the risk of acute kidney injury: a systematic review and meta-analysis

Abstract: BackgroundMounting evidence indicated that the elevated serum uric acid level was associated with an increased risk of acute kidney injury (AKI). Our goal was to systematically evaluate the correlation of serum uric acid (SUA) level and incidence of AKI by longitudinal cohort studies.MethodsWe searched electronic databases and the reference lists of relevant articles. 18 cohort studies with 75,200 patients were analyzed in this random-effect meta-analysis. Hyperuricemia was defined as SUA levels greater than 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 62 publications
2
59
0
2
Order By: Relevance
“…34 Our results also conflict with a number of published studies on the association between uric acid level and the development of AKI or risk for death. 39 Higher uric acid levels have been reported to predict the risk for AKI in hospitalized patients [40][41][42] and after cardiac surgery, [16][17][18] with some reports of a J-shaped association showing higher risk at both very low and high uric acid levels. 43 In the Atherosclerosis Risk in Communities Study, higher uric acid levels predicted risk for a hospital stay with AKI during a mean follow-up of 12 years, although results from Mendelian randomization analyses did not support a causal association.…”
Section: Discussionmentioning
confidence: 99%
“…34 Our results also conflict with a number of published studies on the association between uric acid level and the development of AKI or risk for death. 39 Higher uric acid levels have been reported to predict the risk for AKI in hospitalized patients [40][41][42] and after cardiac surgery, [16][17][18] with some reports of a J-shaped association showing higher risk at both very low and high uric acid levels. 43 In the Atherosclerosis Risk in Communities Study, higher uric acid levels predicted risk for a hospital stay with AKI during a mean follow-up of 12 years, although results from Mendelian randomization analyses did not support a causal association.…”
Section: Discussionmentioning
confidence: 99%
“…H yperuricemia is a metabolic disease with an elevated serum uric acid, resulting from an increased uric acid formation, or reduced renal uric acid excretion, or a combination of both processes. Hyperuricemia not only leads to gout but also paves the way for potential renal damage, diabetes, autoimmune disorders, and cardiovascular diseases (Borghi et al, 2015;Dai et al, 2013;Fang and Alderman, 2000;Feig et al, 2008;Keenan et al, 2012;Sluijs et al, 2013;Xu et al, 2017). Along with the high risk of hyperuricemia worldwide (Kim et al, 2018), its prevalence in China has been increasing rapidly, reported from 1.4% to 13.3%, over the past three decades (Chen et al, 1998;Liu et al, 2014Liu et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Serum uric acid has previously been associated with acute kidney injury in adult patients, including in patients undergoing cardiac surgery. 18,19 Ejaz and colleagues demonstrated that in adults with moderate renal dysfunction and hyperuricemia, rasburicase administered prior to cardiac surgery did not affect post-operative serum creatinine but decreased urine neutrophil-associated lipocalina specific marker of renal tubular injury. 20 The association between uric acid and risk of acute kidney injury in the paediatric cardiac population has not been well studied.…”
Section: Discussionmentioning
confidence: 99%